P121 Rheumatoid synovial fluids differentially affect ADSC proliferation and immunomodulatory potential. (21st February 2018) - Sayegh, ST; Atat, OEl; Moussa, M; Cavaignac, E; Constantin, A; Cantagrel, A; Alaaeddine, N; Davignon, J-L
Abstract : Introduction: Adipose-derived mesenchymal stem cells (ADSC) are currently considered as a potential innovative therapy for rheumatoid arthritis (RA) due to their immune-modulating properties. It has been well established that ADSC exert an immune-regulating response when exposed to an inflammatory environment through the secretion of soluble mediators and cell-cell contact mechanisms. Several molecules are implicated in ADSC-mediated immunomodulation such as PGE2, IDO, IL-6, TGF-β and TSG6. However, while ADSC have shown remarkable results in vitro and in animal models, their efficacy in clinical applications has yet to be fully elucidated. Objectives: Considering the diversity of the local inflammatory microenvironment in the joints of RA patients and to further explore the behaviour of ADSC within their microenvironment, we aimed to study the effect of synovial fluid (SF) collected from patients with RA on ADSC proliferation and immune-modulating properties. Methods: ADSC isolated from 6 healthy subjects were cultured for 24 hours in the presence or absence of RASF (diluted to 5%) obtained from 10 different RA patients or a control SF obtained from a patient undergoing non-inflammatory rheumatism related surgery. ADSC proliferation was assessed by an MTT colorimetric assay. After SF treatment, ADSC were harvested for RNA extraction and subsequent RT-qPCR to quantify the gene expression of COX2, IL6, IDO, TSG6, TGF-β. To evaluate the inflammatory status of SF, pro-inflammatory cytokines present in SF were first identified using an antibody-based membrane array and then quantified by ELISA or CBA. Results: RASF differentially affected the proliferation of ADSC with 2 out of 10 inducing ADSC proliferation whilst the remaining inhibited proliferation. Gene expression of COX2, IDO, IL-6, TSG6 and TGF-β was simultaneously induced in only 4 of the 10 RASF included in this study. We thus investigated if these four RASF had any particular inflammatory signature that could explain their effect on ADSC. Higher concentrations of one or more of the following markers IL-6, TNFα, MCP1, ICAM1, IL1ra were detected in these SF compared to others, which correlates with a more potent pro-inflammatory environment. Conversely, RASF that had no effect on ADSC gene expression presented a less inflammatory profile. Recombinant cytokines and neutralisation assays are underway to determine which specific molecules mediated the SF effect on ADSC. Conclusions: Proper licensing of ADSC to an anti-inflammatory phenotype is usually done in vitro by stimulation with high concentrations of pro-inflammatory cytokines which do not necessarily reflect the concentrations present in the synovial fluid. This study sheds further light on how ADSC respond to local inflammatory stimuli in order to better direct their immunomodulatory ability and efficacy in clinical therapy. Acknowledgements: *N. Alaaeddine and J.-L. Davignon are joint senior authors Disclosure of interest: None declared